Occupational hazards correlates of ocular disorders in Ghanaian fisheries - Samuel Kyei; Andrew Owusu-Ansah; Samuel Bert Boadi-Kusi; Dennis Nii Abbey; Emmanuel Kwasi Abu (PAGEPress Publications, 2016)
The study examined the ocular health of agricultural workers in the fisheries sub sector with the aim of establishing a possible correlation between the work place hazards and their ocular health. A multi-stage random sampling (involving 683 subjects, 358 fishmongers and 325 fishers) was employed. Ocular hazards encountered at the work place included seawater, sand or dust, heat, sunrays and smoke. Exposure to these hazards were found to be associated with ocular irritation (P<0.001), tearing (P<0.001), red eye (P<0.001), gritty sensation (P<0.001), blurred distant vision (P=0.001) and blurred near vision (P=0.001). The development of pterygium was associated with the exposure to sunrays (P=0.042) and heat (P=0.001) among fishmongers. Further analysis using multivariate logistic regression indicated exposure to heat as the most important predictive factor for pterygium (OR=1.951, P=0.003). Exposure to seawater was found to be associated with the development of cataract (P=0.022) among fishermen/fishers. Cataract among fishmongers was rather associated with exposure to heat (P=0.005), sunrays (P=0.035) and sand/dust (P=0.002). Exposure to work place hazards is associated with ocular disorders in the fishing industry of Ghana.